Pengaruh Good Corporate Governance, Pengungkapan Corporate Social Responsibility dan Ukuran Perusahan terhadap Harga Saham - Ranto Ranto; Eliada Herwiyanti; Taufik Hidayat (Jurnal READ (Research of Empowerment and Development), 2022)
The stock price fluctuations that occurred from 2016 to 2018 varied in companies indexed on IDX Growth 30. Some experienced a decline, and some experienced an increase. This activity is an essential factor that companies and investors must consider. The purpose of this study is to determine the effect of good corporate governance, which is divided into three aspects, namely managerial ownership, independent board of commissioners, audit committee board, then disclosure of corporate social responsibility and company size to increase share prices, which is supported by stakeholder theory and agency theory. The population in this study is all companies listed on the Indonesia Stock Exchange. The sample used in this study included companies included in the IDX Growth 30 index from 2016 to 2018. The sample selection technique used the purposive sampling method and analyzed the data using multiple regression analysis techniques. The results show that: (1) Managerial ownership has a significant adverse effect on the increase in stock prices, (2) The independent board of commissioners affects the increase in stock prices, and (3) The audit committee affects the increase in stock prices, (4) Disclosure of corporate social responsibility has an effect the increase in stock prices, and (5) the size of the company affects the increase in share prices.